Brand Attachment: The Moderating Effect of High and Low Involvement Products - Cecilia Ugalde; Inés Küster; Natalia Vila (Journal of Consumer Sciences, 2024)
Brand attachment can be considered one of the predictors of consumer commitment to a brand. Based on this key concept, the type of products can condition the consumer's relationship with the brand. This study analyses the moderating effect that the brand’s involvement (high or low) has on the relationship between brand attachment and some of its antecedents (brand personality, perceived quality, brand awareness, and brand credibility) and effects (brand loyalty, purchase intention, and perceived risk). This causal research, with 1922 valid surveys (simple random sampling procedure), was carried out in three main cities of Ecuador (Quito, Guayaquil, and Cuenca): 1150 high-involvement and 722 low-involvement products. Hypotheses were tested using structural equation models, and multi-sample analysis. Results show that brand personality influences brand attachment and loyalty with a higher moderating effect on products with low involvement. Additionally, brand attachment influences brand loyalty with a higher moderating effect on highly involved products. As practical implications, we state that brand managers of high-involvement products must invest in digital tools that maximize the information available to the public to make decisions. Additionally, low-involvement product brand managers must invest in an identifiable image to make it easy for customers to find their brand. This research adds value because no research has been identified that addresses the study of attachment by comparing its operation in high and low-involvement contexts. It opens future research by introducing new variables in the brand personality scale in combination with that of attachment.